2012
DOI: 10.1111/j.1532-5415.2011.03824.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cognitive Behavioral Therapy for Anxiety Disorders in Older People: A Meta‐Analysis and Meta‐Regression of Randomized Controlled Trials

Abstract: The review confirms the effectiveness of CBT for anxiety disorders in older people but is suggestive of lower efficacy in older than working-age people. The small effect sizes in favor of CBT over an active control condition illustrate the need to investigate other treatment approaches that may be used to substitute or augment CBT to increase the effectiveness of treatment of anxiety disorders in older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
5
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(126 citation statements)
references
References 47 publications
8
110
5
3
Order By: Relevance
“…Thirdly, the CBT arm needed to have included psycho-education, cognitive restructuring, and exposure as treatment components. 15 Finally, studies needed to have used the PSWQ or the PSWQ-A as an outcome measure.…”
Section: Eligibility Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Thirdly, the CBT arm needed to have included psycho-education, cognitive restructuring, and exposure as treatment components. 15 Finally, studies needed to have used the PSWQ or the PSWQ-A as an outcome measure.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…[13][14][15][16] Reviews have also suggested that CBT may be less effective for older adults than it is for younger adults, because of the effect of cognitive decline due to aging and high rates of psychiatric comorbidity. [17][18][19] However, there are two key weaknesses of the evidence base for talking treatments for older adults with GAD: lack of specificity and measurement issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of CBT is to reduce depressive symptoms by challenging and reversing these beliefs and attitudes and encouraging people to change their maladaptive preconceptions and behaviours in real life [87]. Although CBT has been shown to reduce symptoms of anxiety and depression in elderly populations [88,89], the evidence in people with COPD is rather limited [90]. A review based on small studies in people with COPD suggests that there is only limited evidence that CBT is effective in reducing symptoms of anxiety and depression when added to exercise and education [91].…”
Section: Promoting Mental Healthmentioning
confidence: 99%
“…In view of the research evidence highlighted above, one might argue that as anxiety is a potentially treatable condition [69,[136][137][138][139], intervention may prove am important factor in the management of individuals living with cognitive impairment and dementia [2,62,75], with dissemination of information regarding late-life anxiety disorder vital as evidence-based treatments, pharmacological and psychotherapy, are available [43, [131][132][133][134][135][136][137][138][139][140][141]. There are however important caveats to consider.…”
Section: Discussionmentioning
confidence: 99%